Histological and Biochemical Evaluation of Urethral Scar following Three Different Hypospadias Repairs: An Experimental Study in Rabbits - Tan, Xiao-Hui; Liu, Xing; Long, Chun-Lan; Zhang, De-Ying; Lin, Tao; He, Da-Wei; Wei, Guang-Hui (European Journal of Pediatric Surgery, 2018)
Introduction Several urethroplasties have been employed in the surgical treatment of hypospadias. Neourethral strictures are among the most common postoperative complications that often require reoperation.Materials and Methods We created a hypospadias model in New Zealand white male rabbits through a hypospadias-like defect and acute repair. A total of 24 animals were randomly allocated into three groups: tubularized incised-plate urethroplasty (TIPU) group (8), perimeatal-based flap urethroplasty (Mathieu) group (8), onlay island flap urethroplasty (onlay) group (8), and corresponding surgical procedures were immediately performed to reconstruct neourethra. The rabbits were killed postoperatively at 5 days, 2 weeks, 6 weeks, and 3 months, respectively. The penile tissue was harvested for histological and biochemical investigations to evaluate the expressions of transforming growth factor β1 (TGF-β1) and α-smooth muscle actin (α-SMactin) in all groups.Results All rabbits were operated on uneventfully. The amount of collagen content was increased in the Mathieu and onlay groups than in the TIPU group (p < 0.05). Biochemical analysis showed that the expression of TGF-β1 in the TIPU group was decreased compared with the two other groups at 2 or 6 weeks postoperatively (p < 0.01). The expression pattern regarding α-SMactin was similar at 6 weeks or 3 months postoperatively (p < 0.01).Conclusion The neourethra repaired by TIPU was practically resumed to normal anatomy and scarring was less apparent than the two other groups. Therefore, TIPU is considered as a relatively rational approach for hypospadias repair. The activity of fibroblasts has been increased in the long term, which may be the pathogenesis of neourethral stricture following hypospadias repair.
Keywords: hypospadias; rabbits; urethra; urogenital; surgical procedures